Music exposure enhances resistance to Salmonella infection by promoting healthy gut microbiota - Zhu, Clara Y.; Byun, Hyuntae; Do, Elyza A.; Zhang, Yue; Tanchoco, Ethan; Beld, Joris; Hsiao, Ansel; Zhu, Jun (Microbiology spectrum, 2025)
Music therapy is increasingly recognized as a low-cost approach to improving health, but how it works remains unclear. Our study demonstrates that music can positively influence health by altering the gut microbiome. In a mouse model, exposure to Mozart’s Flute Quartet in D Major enhanced the gut microbiota, specifically increasing levels of the beneficial bacterium Lactobacillus salivarius . This probiotic protected mice from Salmonella infection by creating an acidic environment that inhibited pathogen growth. Mozart-treated mice also showed reduced anxiety, better spatial memory, and higher food intake without weight gain, suggesting the benefits of music exposure. These findings reveal a novel link between music, gut health, and disease resistance, suggesting that music therapy could be a promising strategy for enhancing gut microbiota and combating infections, including those caused by drug-resistant bacteria.